INDIVIDUAL NUTRITIONAL SUPPORT FOR PULMONARY TUBERCULOSIS PATIENTS AT VARIOUS STAGES OF SURGICAL TREATMENT - M. V. Lukianova; D. V. Krasnov; D. A. Skvortsov (Туберкулез и болезни лёгких)
Individual, metabolically justified prescription of nutritional support at the various stages of peri-operative period results in the trophologic status normalization in those suffering from disseminated fibrous-cavernous pulmonary tuberculosis when applying collapse surgery.